Weathering the Change How to Improve Hydromet Services in Developing Countries? - Rogers, David P. (World Bank E-Library Archive, 2019)
The societal need for more accurate and reliable weather, climate, and hydrological information is growing fast as population density and migration increases and climate change takes place. Nowhere is this need more acutely felt than in low- and middle-income countries (LMICs). The four environmental risks all have a higher-than-average likelihood of occurrence and are tangibly affecting human well-being, including health and economic prosperity. How can these environmental risks be reduced, and losses avoided? Because weather, climate, and the water cycle know no national boundaries, international cooperation is essential for people and society to get timely access to high quality and actionable information to mitigate the threat of meteorological and hydrological hazards. This international cooperation takes place in what is called the Global Weather Enterprise (GWE), a term coined to describe the totality of activities by individuals and organizations to enable weather information to be created and provided to society. The GWE is a supreme exemplar of the value of international cooperation, public-private management, and scientific technological know-how. This report is arranged as follows: Chapter 1 examines the current state of the GWE, the need for modernizing National Meteorological and Hydrological Services (NMHSs), and the difficulties of sustaining improvements once they occur; Chapter 2 takes an in-depth look at NMHSs, highlighting the unacceptably big gap between the capabilities of the most and least advanced ones; Chapter 3 examines why NMHSs need to focus more on providing the services that their stakeholders need and want; and Chapter 4 provides detailed recommendations for modernizing NMHSs